The Reverse Burden of Proof in Indonesia's Money Laundering: A Review - Adinda Putri Jade; Yaris Adhial Fajrin; Diah Nadia Putri; Aisya Sanghra Devi Nugraha (University of Jember, 2020)
Money laundering has become one of Indonesia's serious criminal offenses. Then, cases related to it should proceed under the specific regulation and procedure. In Indonesia, money laundering is a further crime preceded by predicate offenses. In practice, there are two main problems to apply in money laundering: first, the principles' difference between national and international criminal laws, and second, their norm contradiction. Although the money laundering crime is claimed to be a further crime, it is separated from the preceded crime in prosecution, investigation, and evidence. This study aims to review the juridical contention of the reverse burden of proof in money laundering by considering the existing challenges to apply the norms. This study confirms that there is a juridical problem in the reversal of proof mechanism in money laundering. Therefore, the government should harmonize the existing laws relating to the reverse of the burden of proof in money laundering. It is essential to reform the existing regulations by harmonizing laws related to this case. It considers the existing fragmented criminal provisions set out in the Criminal Code and special laws to indicate serious crimes. This harmonization contributes to restoring the return of the state's losses resulted from this crime. Regulatory reform is inevitable. The government then needs to strengthen diplomatic relations with other countries, especially to enforce national laws through Mutual Legal Assistance (MLA) and extradition of money laundering perpetrators. KEYWORDS: Indonesian Money Laundering, Money Laundering Act, Reverse Burden of Proof.